Investigating Organizational Culture among Civil Servants Organizational Commitment - Tubagus Hkualizaman; Hamidah Hamidah; Agung Wahyu Handaru (Fakultas Ekonomi, Universitas Negeri Jakarta, 2018)
This study aims to explore the effects of Organizational Culture on organizational commitment of Civil Servants in an Indonesia context. The sample comprised of 71 Civil Servants working at Cilegon City Government in Indonesia which were selected by a multistage stratified sampling method. A scale that aimed to measure the Civil Servant's Organizational Culture and their organizational commitment was used to collect data. Mean scores, Pearson moment correlation coefficients, and simple linear regression analyses were carried out to analyze data. The Findings Short that Positive relationships between organizational culture and organizational commitment. The results indicated that organizational culture was a significant predictor of organizational commitment.